Heavy metals removal in animal wastewater using water hyacinths (Eichhornia crassipes) - Yong, Sue Yen (Universiti Malaysia Sarawak, UNIMAS, 2007)
Animal wastewaters contain heavy metals which were due to their presence in animal’s diet. This study was conducted to observe the uptake of a mixture of heavy metals such as copper (Cu), cadmium (Cd), lead (Pb) and zinc (Zn) by water hyacinths for a period of four days and leaching of heavy metals in treated and untreated wastewater using living and dead water hyacinths for a period of 7 days. Simultaneously, blank experiments were carried out for comparison. Water hyacinths accumulated higher concentration of heavy metals in the root than in the stems and leaves. The results of the present study showed that Cd absorption was the lowest compared to other metals due to its toxicity. The absorption of Zn and Cu was due to their role as micronutrients and the absorption of Cu ranged from relatively low to relatively high. There was a considerable amount of Pb being absorbed by water hyacinths the roots of water hyacinths. Generally, in Experiment 2, only Cd and Cu was leached whereas in Experiment 3, Cd, Cu and Zn was leached. However, the amount of heavy metals leached was little compared to the absorption. Thus, water hyacinth can be regarded as a heavy metal decontaminator in animal wastewater treatment, rather than as a pollutant.